Factors associated with changes in flavored tobacco products used: Findings from wave 2 and wave 3 (2014–2016) of the population assessment of tobacco and health (PATH) study. (July 2022) - Bansal-Travers, Maansi; Rivard, Cheryl; Silveira, Marushka L.; Kimmel, Heather; Poonai, Karl; Bernat, Jennifer K.; Jackson, Kia; Rudy, Susan; Johnson, Amanda; Cullen, Karen A.; Goniewicz, Maciej; Travers, Mark; et al.
Highlights: Flavored tobacco product use is prevalent across all non-cigarette tobacco products, with fruit being the most popular flavor among youth, young adults, and adults. Our study found stability in the number of flavors and specific flavor used among adult tobacco users. Young adults and youth tobacco users more commonly used products of multiple flavors and changed specific flavors used over time. Abstract: Introduction: Flavored non-cigarette tobacco product use is widespread in the U.S. The availability of flavor options could be playing a role in recent increases in use, especially for non-cigarette tobacco products, among youth and young adults. Little is known about specific flavor preferences of youth and adult flavored tobacco product users, as well as how preferences may change over time. Methods: This study analyzes PATH Study data from completed Wave 2 (2014–2015) and Wave 3 (2015–2016) youth (12–17 years), and adult (18 + years) interviews to estimate the prevalence of flavored non-cigarette tobacco product use. We assess flavor switching by examining changes between flavors and characteristics of those who changed flavors between waves. Results: Across age groups, and at both waves, fruit-flavored products were the most frequently used flavor by past 30-day electronic nicotine delivery systems (ENDS), cigar, cigarillo, and hookah users. In the past 30 days, a higher proportion of youth and young adults used candy/sweets-flavored ENDS than adults. Among adult ENDS users, the odds of changing flavors were highest among younger users and decreased with increasing age. Conclusions: Flavored tobacco product use is prevalent across non-cigarette tobacco products. Stability in the number of flavors used, as well as specific flavors, is higher among adult tobacco users, while the use of multiple flavors, and change in specific flavor, is more prevalent among youth tobacco users. Additional longitudinal research can further examine the role flavors play in appeal, product trial, and switching.